Grid computing the savvy manager's guide - Plaszczak, Pawel; Wellner, Richard (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2006)
A decade ago, the corporate world viewed grid computing as a curiosity. Today, it views it as an opportunity--a chance to reduce costs, improve performance, fund new projects, and take advantage of under-utilized capacity. The engineering behind this transformation has been amply documented. Until now, however, little has been written to prepare managers, executives, and other decision-makers to implement grid computing in a sensible and effective way. Grid Computing: The Savvy Manager's Guide examines the technology from a rigorous business perspective, equipping you with the practical knowledge you need to assess your options and determine what grid computing approach is right for your enterprise. This book is heavy on real-world experience, distilling from a rich assortment of case studies the best practices currently at work in a variety of industries. Always attentive to grid computings many competitive advantages, it is also realistic about the challenges of selling the idea to staff and making it a part of your companys culture. Grid Computing has an Online Companion at www.savvygrid.com with contents, details, community forum, and latest updates for the material. * Sketches the history of grid computing, showing how it made the leap from academia to business. * Examines the criteria you'll need to meet to make your network "grid-enabled." * Explains how a grid-based solution can be made to meet key organizational requirements, including security, scheduling, data storage, and fault-tolerance. * Surveys the approaches currently available and helps you choose the one that will best meet your needs, both now and in the future. * Focuses heavily on the competitive advantages you can reap from grid computing, and provides advice on convincing your organization to adopt grid computing and making a successful transition.
Introduction -- The basics -- Grid computing enters business -- Joining the grid -- Technical issues -- Management issues.
Includes bibliographical references and index.
Keywords: Computational grids (Computer systems).; Electronic books